2020
DOI: 10.1111/pce.13730
|View full text |Cite
|
Sign up to set email alerts
|

Far‐red photons have equivalent efficiency to traditional photosynthetic photons: Implications for redefining photosynthetically active radiation

Abstract: Far-red photons (701-750 nm) are abundant in sunlight but are considered inactive for photosynthesis and are thus excluded from the definition of photosynthetically active radiation (PAR; 400-700 nm). Several recent studies have shown that far-red photons synergistically interact with shorter wavelength photons to increase leaf photochemical efficiency. The value of far-red photons in canopy photosynthesis has not been studied. Here, we report the effects of far-red photons on single leaf and canopy photosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
184
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(204 citation statements)
references
References 66 publications
17
184
3
Order By: Relevance
“…Despite the classic definition of PAR, recent studies indicate that far-red photons (700-750 nm) are photosynthetically synergistic with shorter wavelength photons 51,52 . These photons are thus being reconsidered for their role in photosynthesis.…”
Section: Spectral Effects On Plant Shape and Photosynthesismentioning
confidence: 99%
“…Despite the classic definition of PAR, recent studies indicate that far-red photons (700-750 nm) are photosynthetically synergistic with shorter wavelength photons 51,52 . These photons are thus being reconsidered for their role in photosynthesis.…”
Section: Spectral Effects On Plant Shape and Photosynthesismentioning
confidence: 99%
“…Whole-plant gas exchange measurements of 16 C 3 and two C 4 species under red/blue light and red/blue plus FR light indicated that adding far-red photons (10 -30 % of PPFD) caused similar increases in the whole canopy photosynthetic rate as adding the same amount of red/ blue photons (Zhen & Bugbee, 2019). To demonstrate that far-red photons are equally efficient at driving photosynthesis, the authors grew lettuce under spectra with or without 15 % of far-red photons at the same total photon flux, and the results at harvest showed 35 % higher dry biomass in treatments with far-red photons, which was almost entirely caused by enhanced radiation capture through leaf expansion.…”
Section: Photosynthesis and Biomass Produc-tionmentioning
confidence: 93%
“…Recently, Zhen and van Iersel (2017) found a synergistic interaction between far-red light and PAR, specifically an increase in net photosynthesis of lettuce (Lactuca sativa) in response to added far-red light. Zhen and Bugbee (2020) found that adding far-red light (up to 40% of PAR) increased canopy photosynthesis of 14 diverse agronomic and horticultural crop species as much as adding the same photon flux of PAR.…”
mentioning
confidence: 97%
“…This has the potential to shorten cropping cycles of ornamental plants grown in controlled environments. One approach to enhancing growth is to include far-red light (l = 700-800 nm) in the spectrum because 1) farred light can trigger a shade-avoidance and/or acclimation response (Franklin, 2008;Keuskamp et al, 2010;Possart et al, 2014) and 2) it is photosynthetically active (Zhen and Bugbee, 2020;Zhen and van Iersel, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation